The Impact of Shift Work and Job Fatigue on Employee Performance (Case Study of Assembly Division Employees at PT Tokai Rika Indonesia) - Rinto Rivanto; Ega Oktaviana (Universitas Mohammad Husni Thamrin, 2026)
This study aims to determine the effect of Work Shifts and Work Fatigue on the Performance of Assembly Division Employees at PT. Tokai Rika Indonesia. the number of respondents in the study conducted was 77 employees of the Assembly Division at PT. Tokai Rika Indonesia. The method used in this study is a quantitative research method using a descriptive approach . The data analysis used in this study was using SPSS 26 software. The analysis technique uses multiple regression analysis with the smallest square equation and the hypothesis test uses t-statistics and F test to test the regression coefficient partially and simultaneously, validity test, reliability, as well as classical assumption test which includes normality test, multicolonierity test, heteroskedasticity test and autocorrelation test. The results showed that there was a positive and significant influence of Work Shifts on Employee Performance. This is seen based on the results (t test) with a calculated t value > t table of 2,477 > 1,992 and a signification value of 0.016 < 0.05. Then there is a positive and significant influence of Work Fatigue on Employee Performance. This is seen based on the results (t test) with a calculated t value > t table which is 3,604 > 1,992 and a signification rate of 0.001 < 0.05. And, together there is the effect of Work Shifts and Work Fatigue on Employee Performance. This is seen based on the results (test F) with the value of F calculating > F table which is 84,267 > 3,120 with a signification rate of 0.000 < 0.05. From the results of the analysis, a coefficient determination value (R2) of 0.687 was also obtained, indicating that Work Shift and Work Fatigue were able to explain 68.7%. While the remaining 31.3% was explained by independent variables that were not included in this study.